Papers - Mining - Geophysical Surveys at the Malachite Mine, Jefferson County, Colorado (T. P. 1947) - C. A. Heiland; Tripp R. M.; Dart Wantland (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1946)
This paper serves to illustrate the application of geophysics to a virtually abandoned mine properly, an application that led to the discovery of an ore body and thus afforded an Opportunity to cOmpare subsequent geologic findings with geophysical data. The work herein described represents, however: more than mere ''case history." It demonstrates that it is possible to obtain satisfactory results by simple means and relatively inexpericnced personnel. The geophysical surveys were made by students as a part of their field assignments in the course of their regular training, and were supervised by Dart Wantland, J. E. Hawkins and R. Maurice 'Tripp. In the course of several seasons an appreciable amount of material was accumulated, which gave graduate students an opportunity for special studies. In this connection, the contributions by L. Massé, R. C. Hyslop, and J. E. Hawkins deserve special mention. The property owners cooperated wholeheartedly in the work, and special thanks are due messrs. J. F. Johnson and S. E. Zelenkov, of the American Smelting and Refining Co., for their interest and for permission to utilize the results of their development work for this publication. Location and Geology The Malachite mine is situated on the northcrn slope of Bear Creek Canyon, 4 miles northeast of Evergreen, I½ miles northwest of Idledale, and 4% miles west northwest of Morrison, in Jefferson County, Colorado. The location (Fig. I) is north of the center of set. 30, T. 45, R. 70 W., at an elevation of about 7500 ft, above sea level, Near the mine the terrain slopes rather uniformly southward at an angle of about 180 pigs. 3 and 7). The geology of the Malachite mine area has been described by J, underhill,' W, Lindgren,2 and J. Boyd.3,4 A map showing surface outcrops and mine workings appears in Fig, 2. the Malachite mine is in an amphibolite belt enclosed in gneisses and schists of the Idaho-Springs formation (probably early Algonkian age). The highly contorted beds are nearly vertical and strike slightly north of west. A series of granite-pegmatite dikes have been intruded almost at right angles into the gneisses and schists and doubtedless are postmineral. While most of the formations are exposed at the surface, a part of the 'lope is covered by slide rock and float, and in the eastern portion by alluvium and creek fill. A quartz-diorite dike cuts through the amphibolite schists at a small angle with nearly vertical dip. The copper sulphides, developed in this dike by magmatic segregation, occur in lenticular form. As far as the mine workings have revealed, the ore lenses are often discontinuous in depth and